FUNDAMENTALS OF WOOD MATERIALS AND HAND PROCESSING TECHNOLOGIES - Abdullaev, Tolkinali; Siddikova, Ranokhon (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This research article presents ideas on interactive methods recommended for use in technology lessons and their content. Examples of modern methods and various types of interactive methods are provided.